CORRELATION-REGRESSION ANALYSIS MODELS OF SOCIO-ECONOMIC PROCESSES - Muminova Makhbuba Abduvafoevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes socio-economic processes correlation-regression analysis models and correlation-regression analysis models, least squares method, calculation and estimation of regression equation, elasticity coefficient, calculation of confidence intervals.